Classroom coliving climate: nature, measurement, effects and implications for social education. A cross-cultural study - Alonso Tapia, Jesús; Simón, Cecilia; López-Valle, Nuria; Ulate, María Alexandra; Biehl, María Loreto (Anales de Psicología / Annals of Psychology, 2019)
This paper has three objectives, after proposing an initial model of classroom coliving climate: to develop two measures to test its validity, to test their usefulness for analyzing differences between classrooms, and to do it in two different countries. The initial model includes seven interaction patterns that, if present, favor the students’ social inclusion. The first questionnaire assesses the classroom coliving climate perceived by the student, and the second, the degree in which the student interacts according to the model. Participants were 2581 Secondary-School students, 2038 from Costa Rica and 543 from Spain. To test model-fit, confirmatory factor analyses, cross validation and multi-group analyses were carried out. Correlation and regression analyses were also carried out to determine discriminant and concurrent validity using as criteria a measure of social integration. ANOVA analyses were used to test for differences between classrooms (η2 between .19 and .28). Results, similar in both countries, showed that both questionnaires had adequate structural validity (CFI between .94 and .97), and discriminant and concurrent validity (r predictors-criterion between .37 and .44; p < .0001). Due to the nature of their content, the questionnaires can be used for planning interventions aimed at improving coliving, and for assessing their effectiveness.